FTO regulates the chemo‐radiotherapy resistance of cervical squamous cell carcinoma (CSCC) by targeting β‐catenin through mRNA demethylation. Issue 5 (1st February 2018) - Zhou, Shun; Bai, Zhou‐Lan; Xia, Di; Zhao, Zhi‐Jun; Zhao, Ren; Wang, Yan‐Yang; Zhe, Hong
Abstract : The role of N 6 ‐methyladenosine (m 6 A) demethylase fat mass and obesity‐associated protein (FTO) in the regulation of chemo‐radiotherapy resistance remains largely unknown. Here, we show that the mRNA level of FTO is elevated in cervical squamous cell carcinoma (CSCC) tissues when compared with respective adjacent normal tissues. FTO enhances the chemo‐radiotherapy resistance both in vitro and in vivo through regulating expression of β‐catenin by reducing m 6 A levels in its mRNA transcripts and in turn increases excision repair cross‐complementation group 1 (ERCC1) activity. Clinically, the prognostic value of FTO for overall survival is found to be dependent on β‐catenin expression in human CSCC samples. Taken together, these findings uncover a critical function for FTO and its substrate m 6 A in the regulation of chemo‐radiotherapy resistance, which may bear potential clinical implications for CSCC treatment.